2006
DOI: 10.2164/jandrol.05143
|View full text |Cite
|
Sign up to set email alerts
|

The Length of the Spermatogenic Cycle Is Conserved in Porcine and Ovine Testis Xenografts

Abstract: Xenografting of immature mammalian testis tissue into mice can accelerate sperm production. To determine whether this shortened time to sperm production is because of reduced length of the spermatogenic cycle, we applied bromodeoxyuridine (BrdU) incorporation to analyze the spermatogenic cycle in porcine and ovine testis xenografts. Small testis fragments from newborn pigs and sheep were ectopically grafted into mice. Once complete spermatogenesis was present in grafted tissue, mice were injected with BrdU a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 25 publications
3
37
0
1
Order By: Relevance
“…The timing of appearance of spermatocytes or spermatozoa in the xenografts was similar to those observed in developing boars [33,34]. Zeng et al [35] demonstrated that the length of the spematogenic cycle in porcine xenografts implanted into immunodeficient mice was about 9 days, which is similar to that observed in boars [33,36]. However, spermatogenesis in the grafted tissues did not reach the quantitatively normal levels observed in young adult boars.…”
Section: Discussionsupporting
confidence: 56%
“…The timing of appearance of spermatocytes or spermatozoa in the xenografts was similar to those observed in developing boars [33,34]. Zeng et al [35] demonstrated that the length of the spematogenic cycle in porcine xenografts implanted into immunodeficient mice was about 9 days, which is similar to that observed in boars [33,36]. However, spermatogenesis in the grafted tissues did not reach the quantitatively normal levels observed in young adult boars.…”
Section: Discussionsupporting
confidence: 56%
“…Table 2 shows that the percentage of xenografts recovered from recipient mice decreased as donor age increased and that the percentage of the xenografts containing germ cells at different stages of spermatogenesis varied with both donor age and the retrieval time points. For the 8-and 9-16-week-old donor age groups in our study, we had a percentage recovery rate very similar to that reported for other species (Rathi et al 2005;Zeng et al 2006).…”
Section: Discussionsupporting
confidence: 87%
“…Spermatocytes were observed in approximately one-third of the xenografts 10 weeks after the procedure in the 8-week-old donor group, as opposed to typically appearing at age 5-6 months. This has been noted by others (Oatley et al 2005;Rathi et al 2005;Zeng et al 2006) working not only with species in which sperm production is accelerated, but also species in which sperm production occurs at approximately the same time as in age-matched control testes. The most likely explanation for this early onset of meiosis is that the xenograft tissue is suddenly exposed to an adult endocrine profile in the recipient mouse and the germ cells are able to respond (Honaramooz et al 2002;Schlatt et al 2003;Rathi et al 2005).…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, in large domestic animals, testicular xenografting into under skin of back of immunodeficient animals such as nude mice or SKID mice has been conducted. To date, sperm have been obtained from testicular grafts of several species after ectopic xenotransplantation (pig [52][53][54]; goat [52]; cat [55]; and rhesus monkey [56]). In our study [57], we obtained testicular tissues from 5 days old piglet ( Fig.…”
Section: Icsi With Sperm Grown In Testicular Tissues Xenografted Intomentioning
confidence: 99%